KESANTUNAN DALAM PELAYANAN STUDI KASUS PADA PUSAT PERBELANJAAN ISETAN - I Gede Oeinada (Journal Social and Humaniora, 2017)
politeness. It can be seen from the choice of di?erent vocabulary selected for use by speakers in accordance with the context of use (place, time, and hearer). Politeness not only be seen from the speech (verbal), but is also reflected in the movements (nonverbal) speakers. This paper aims to express politeness both verbal and nonverbal language in the service implemented by the waiter at the shopping center ISETAN Urawa, Japan in serving visitors. This research is a descriptive case study using the techniques in interviews and direct observation in data collection. The results showed that the waiters in ISETAN Urawa, Japan utilizing both verbal and nonverbal means to bring civility to the partner language he said that the visitors of the shopping center. In addition, the waiters previously have received adequate training before being assigned to serve the visitors. There is a cultural concept that is invisible behind it that is appreciated meeting with other people (? ? ? ? ichi go ichi e). Key words: politeness verbal, nonverbal politeness, ISETAN